ANALISIS PERBUATAN MALPRAKTIK DOKTER DALAM PERSPEKTIF HUKUM PIDANA - Syamsu Rizal S (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2018)
In achieving and realizing these national goals, sustainable development has been carried out in various fields, including in this case development in the health sector, and this includes health care and health services by medical personnel. This health care right does not appear suddenly. This research was a normative legal research that was prescriptive and technical or applied. The research approach uses a law approach and a case approach. The type of research data is secondary data with primary legal materials and secondary legal materials. Data collection techniques in the form of library study and data analysis techniques used are deductive. The results of the study obtained by the author in conducting this research was that malpractice can be categorized as unlawful acts based on the formulation of Article 1365 BW, there are four conditions that must be met to demand the loss of unlawful acts, of course, including medical law malpractice that qualifies as illegal acts and Legal remedies that can be carried out by patients if they experience malpractice can be achieved through two channels, namely litigation (court) and non-litigation (outside court).